2022
DOI: 10.3389/fpls.2022.1036764
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic DNA methylation changes reveal tissue-specific gene expression in sugarcane

Abstract: DNA methylation is an important mechanism for the dynamic regulation of gene expression and silencing of transposons during plant developmental processes. Here, we analyzed genome-wide methylation patterns in sugarcane (Saccharum officinarum) leaves, roots, rinds, and piths at single-base resolution. DNA methylation patterns were similar among the different sugarcane tissues, whereas DNA methylation levels differed. We also found that DNA methylation in different genic regions or sequence contexts plays differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…S5 , see online supplementary material) demonstrated high consistency among replicates. In conclusion, the quality and depth of our sequencing data were excellent compared to other experiments [ 26 , 27 ] and can be used for subsequent studies.…”
Section: Resultsmentioning
confidence: 51%
“…S5 , see online supplementary material) demonstrated high consistency among replicates. In conclusion, the quality and depth of our sequencing data were excellent compared to other experiments [ 26 , 27 ] and can be used for subsequent studies.…”
Section: Resultsmentioning
confidence: 51%
“…Allele‐specific DNA methylation was found to cause differential expression of alleles during maize endosperm development (Xu et al., 2022). Additionally, DNA methylation (Wang et al., 2015, 2018; Xu et al., 2022; Xue et al., 2022), histone modifications (Guo et al., 2015), non‐coding RNAs function (O'Neill, 2005; Rong et al., 2005), and cis ‐ or trans ‐regulation (Zhang & Borevitz, 2009) are also involved in the ASEs, and further studies are needed to investigate these mechanisms in P. championii .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the present study found that under conditions of varying sink strengths (removing all fruits or retaining one fruit on a plant), it was also able to alter the DNA methylation pattern in cucumber source leaves. Moreover, DNA methylation has been studied in more detail in sucrose-transporting plants [ 30 , 31 ], but very little in RFO-transporting plants. Meanwhile, we externally applied 5-Aza-dC, a widespread DNA methylation inhibitor, on FNLs, and found that it could increase stachyose synthase ( CsSTS ) gene expression, enzyme activity and stachyose content in the RFO synthesis pathway of source leaves and increase fruit length and dry weight, which further verified that DNA methylation promotes fruit enlargement by regulating RFO synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that DNA methylation modulates gene expression in the pre- and post-transcriptional regulation of several biological processes, including the vernalization response, defense against parasitic elements, and stress responses [ 25 , 26 , 27 , 28 , 29 ]. Recent research has shown that DNA methylation affects the expression of genes related to starch and sucrose metabolism, photosynthesis, and plant hormone signal transduction, as well as stress response in sucrose-transporting crops, such as apple and sugarcane [ 30 , 31 ]. However, the role of DNA methylation in sink-source regulation in crops that rely on RFOs as the major transport form of photoassimilates in vivo has not been reported.…”
Section: Introductionmentioning
confidence: 99%